Alcune considerazioni sull’ipotesi di Sapir-Whorf applicata alla traduzione dei termini costituzionali italiani e spagnoli nell’ ottica comparativo-contrastiva - Brugnoli, Patrizia (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
The main aim of this article is to contribute to raising the interest around legal language, rarely analysed in the Italian-Spanish translation perspec¬tive. In particular, the author ’s interest is concentrated on specific normative texts, the Italian and Spanish Constitutions, of which she takes some lexical features into account. The article shows, through the use of componential analysis, that the “translatability” of the above mentioned traits of legal text from one language to another is impossible, even for those languages which are considered “similar” like Spanish and Italian. In Linguistics this hypoth¬esis was supported by Sapir- Whorf and is particularly true if applied to the legal language. In fact, legal translation is “culture-bond” and it is inti¬mately related to the socio-economic structures which are peculiar to a country.